A phase 1/2 study of lenalidomide with low-dose oral cyclophosphamide and low-dose dexamethasone (RdC) in AL amyloidosis - Kastritis, E.; Terpos, E.; Roussou, M.; Gavriatopoulou, M.; Pamboukas, C.; Boletis, I.; Marinaki, S.; Apostolou, T.; Nikitas, N.; Gkortzolidis, G.; Michalis, E.; Delimpasi, S.; et al. (Blood, 2012)
In this phase 1/2 study, we explored the feasibility and activity of an oral regimen of lenalidomide with low-dose dexamethasone and low-dose oral cyclophosphamide (RdC) in patients with primary systemic light chain amyloidosis. RdC was given for up to 12 cycles in prespecified cohorts at escalated doses: 13 patients were treated in phase 1 and 24 in phase 2; 65% were previously untreated, and most had renal and/or cardiac involvement and elevated cardiac biomarkers. Lenalidomide 15 mg/d and cyclophosphamide 100 mg/d were further evaluated in phase 2. On intention to treat, 20 (55%) patients achieved a hematologic response, including 3 (8%) complete remissions. Hematologic responses were seen at all dose levels and in 4 of 5 patients who had received bortezomib previously. An organ response was recorded in 22% of patients on intention-to-treat and in 40% of patients who survived at least 6 months. The median time to progression was 10 months and the 2-year survival was 41%. Fatigue, nonneutropenic infections, and rash were the most common toxicities. The results of the present study show that RdC is an oral regimen with activity in primary systemic light chain amyloidosis and may be an additional treatment option, especially for patients with preserved organ function or for patients who cannot receive or who relapse after bortezomib. This study is registered at www.clinicaltrials.gov as NCT00981708. © 2012 by The American Society of Hematology.